Learning Typology in Arabic Language Learning (International Journal of Education and Literature, 2025)
This study aims to examine learning typologies in Arabic language instruction and analyze how differences in learning styles influence the effectiveness of the learning process. The study focuses on identifying the characteristics of visual, auditory, and kinesthetic learning types and how these variations can serve as the basis for designing more adaptive and meaningful Arabic teaching strategies. The method employed is a literature review, involving the examination of books, journal articles, previous research findings, and other relevant scientific documents. The analysis was conducted through the collection of references, in-depth review, critical evaluation, categorization of findings, and theoretical synthesis, resulting in a comprehensive description of learning typologies within the context of Arabic language learning. The findings indicate that Arabic language learning is influenced not only by variations in learning typologies but also by fundamental conceptual foundations of learning, which include philosophical, psychological, sociological, and communicative aspects. Learning typologies visual, auditory, and kinesthetic play a significant role in determining how learners understand and respond to Arabic material. Furthermore, learning success is strongly shaped by the application of active learning principles and the learners' cognitive processes. The cognitive domain, which refers to mental abilities to think, establish associations, understand, and analyze knowledge, becomes a crucial element in optimizing language comprehension. These findings affirm that Arabic language learning will be more effective when teachers are able to integrate fundamental learning concepts and adapt teaching strategies to learners' typologies and cognitive abilities.